Investigation of the Dielectric Properties of Graphite and Carbon Black-Filled Composites as Electromagnetic Interference Shielding Coatings - ARCA, EMİN (My University, 2023)
The main purpose of electromagnetic interference (EMI) shielding coatings is the insulation of sensitive devices and protect people from electromagnetic field exposure due to its effects on the human body. This paper investigates the dielectric properties, and electromagnetic shielding performances of graphite and carbon black (CB) filled epoxy matrix composites produced by the mechanical mixing method. The sample compositions were created at rates ranging from 1 to 7 wt%. Samples were analyzed by Vector Network Analyzer (VNA) using the coaxial method in the range of 1–14 GHz, including L band, S band, C band, X band and partially Ku band. After determining the scattering parameters with VNA, AC conductivity, absorption, reflection and total shielding efficiency values were calculated. At high frequencies, almost all the samples showed higher AC conductivity. CB-filled samples show higher AC conductivity than graphite-filled samples. The total shielding efficiency (SET) of the graphite-added samples (19–21 dB) is slightly higher than the carbon black-added samples (8–17 dB). Distinct filling ratios in graphite-added samples result in closer shielding behavior in contrast to carbon black-added samples. However, higher shielding efficiency is observed as the CB filler ratio increases. The shielding efficiencies of the samples with both types of filling materials vary little depending on the frequency. Reflection is the main mechanism of the shielding efficiency, which constitutes the majority of total efficiency for all types of samples.
Keywords: Bilgisayar Bilimleri; Kimya Mühendisliği ve Teknolojisi; Kimya; Diğer; Temel Bilimler; Mühendislik ve Teknoloji; Computer Sciences; Chemical Engineering and Technology; Chemistry; Other; Natural Sciences; Engineering and Technology; Mühendislik, Bilişim ve Teknoloji (ENG); Temel Bilimler (SCI); Bilgisayar Bilimi; Mühendislik; Malzeme Bilimi; ALETLER & GÖSTERİM; MÜHENDİSLİK, KİMYASAL; KİMYA, UYGULAMALI; Engineering, Computing & Technology (ENG); Natural Sciences (SCI); COMPUTER SCIENCE; ENGINEERING; MATERIALS SCIENCE; CHEMISTRY; INSTRUMENTS & INSTRUMENTATION; ENGINEERING, CHEMICAL; CHEMISTRY, APPLIED; Genel Malzeme Bilimi; Fizik Bilimleri; Enstrümantasyon; Genel Mühendislik; Proses Kimyası ve Teknolojisi; Bilgisayar Bilimi Uygulamaları; Akışkan Akışı ve Transfer İşlemleri; General Materials Science; Physical Sciences; Instrumentation; General Engineering; Process Chemistry and Technology; Computer Science Applications; Fluid Flow and Transfer Processes; carbon black; coating; composites; electromagnetic interference shielding; graphite